2023
DOI: 10.3389/fpubh.2023.1183725
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence-driven prediction of COVID-19-related hospitalization and death: a systematic review

Abstract: AimTo perform a systematic review on the use of Artificial Intelligence (AI) techniques for predicting COVID-19 hospitalization and mortality using primary and secondary data sources.Study eligibility criteriaCohort, clinical trials, meta-analyses, and observational studies investigating COVID-19 hospitalization or mortality using artificial intelligence techniques were eligible. Articles without a full text available in the English language were excluded.Data sourcesArticles recorded in Ovid MEDLINE from 01/0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…While there was no significant change in classification (the national percentage of rural and urban populations remained consistent with the 2010 definition), the underlying population shift by the new definition could have introduced bias in our current findings [66]. Even though there has been a demonstration of good prediction with AI models when studying mortality and hospitalization rates for certain health conditions such as COVID-19, there could be concerns about replicability and the bias inherent in the study [7], including ours.…”
Section: Limitation Of Our Studymentioning
confidence: 83%
See 1 more Smart Citation
“…While there was no significant change in classification (the national percentage of rural and urban populations remained consistent with the 2010 definition), the underlying population shift by the new definition could have introduced bias in our current findings [66]. Even though there has been a demonstration of good prediction with AI models when studying mortality and hospitalization rates for certain health conditions such as COVID-19, there could be concerns about replicability and the bias inherent in the study [7], including ours.…”
Section: Limitation Of Our Studymentioning
confidence: 83%
“…AI tools could also play a big role in identifying high-risk populations for hospital injury and guide interventions and preventive actions to improve patient safety [6]. Recent applications of AI in this domain have been in predicting hospitalizations and determining the mortality associated with COVID-19 [7,8]. The prospects and benefits of AI and machine learning use are well recognized and accepted in healthcare today concerning disease diagnosis, risk assessment associated with morbidity and mortality, surveillance of infectious diseases and outbreak prediction, and policy implications [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…AI-powered epidemiological models have become invaluable tools in predicting the transmission of viruses, including COVID-19. Furthermore, AI-based techniques can be utilized to track and monitor the spread of viruses at different scales, ranging from individual to population levels [99].…”
Section: Epidemiological Forecastingmentioning
confidence: 99%
“…Heterogeneity of populations and risk factors across geographical settings ( 10 ), including the effects of social determinants and their interplay ( 14 ) and the lack of validation of prognostic tools in multiple cohorts ( 17 ) has played a key role for lack of robustness and generalizability in performance across populations and settings. We recently conducted a systematic review and found that previous machine learning and artificial intelligence (AI)-based predictive models for COVID-19 hospitalization and mortality were affected by a high risk of bias or lack of applicability, especially due to lack of external validation of prognostic models ( 18 ). Of note, there are examples of studies that have developed AI-driven models for COVID-19 hospitalization or death, which underwent external validation ( 19 , 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Of note, there are examples of studies that have developed AI-driven models for COVID-19 hospitalization or death, which underwent external validation ( 19 , 20 ). However, it is worth mentioning that we consider these studies as having a high risk of bias ( 18 ). Therefore, this study aimed at overcoming the limitations of the previously developed AI models by more stringently identifying predictors of COVID-19 severity and using them to develop a disease risk score (DRS) for COVID-19-related hospitalization and for COVID-19 death – overall and across the COVID-19 waves – for residents in Sweden, and externally validate the DRS in Norway.…”
Section: Introductionmentioning
confidence: 99%